Achalasia-associated superior mesenteric artery syndrome with massive gastric dilatation - Zaim Gashi; Leutrim Shabani; Endrit Shatrolli (European Journal of Case Reports in Internal Medicine)
Background: Achalasia and superior mesenteric artery (SMA) syndrome are both uncommon gastrointestinal disorders. When they occur together—a rare clinical scenario—they can cause serious complications, including severe gastric distension. Case Presentation: We report the case of a 62-year-old man with a known history of achalasia, previously managed with botulinum toxin injections. He presented with progressively worsening abdominal bloating, unintentional weight loss, and abdominal discomfort. Endoscopy revealed a strikingly dilated oesophagus and stomach, filled with nearly 9 litres of fluid. Further imaging with computed tomography angiography showed a narrowed aortomesenteric angle measuring just 16.7°, consistent with a diagnosis of SMA syndrome. Remarkably, despite the massive distension, no perforation was identified. Discussion: This case highlights a rare but important overlap between achalasia and SMA syndrome, leading to extreme gastric dilatation in the absence of rupture. Despite the extreme degree of gastric dilatation observed on both endoscopy and imaging, the stomach wall remained intact, and there were no signs of ischemia or perforation. Although SMA syndrome may occur secondary to other health conditions, this case underscores how variable and potentially dangerous this dual pathology can be. Conclusion: Clinicians should remain vigilant for the possibility of SMA syndrome in patients with achalasia who develop new or worsening upper gastrointestinal symptoms, particularly if there is significant gastric dilatation. Early imaging and recognition can be crucial in preventing severe outcomes like perforation.